Postharvest fruits: maturation, softening and transcriptional control - Martínez-González, Mónica Elizabeth; Balois Morales, Rosendo; Alia-Tejacal, Irán; Cortes-Cruz, Moises Alberto; Palomino-Hermosillo, Yolotzin Apatzingan; López-Gúzman, Graciela Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2017)
The process of fruit formation requires a complex series of gene interaction and signaling pathways for the conversion of a flower ovary into a fruit. In fleshy fruits it involves the growth, development and maturation of the fruit. The objective of this review is to compile the information on relevant research related to the ripening, softening and transcriptional regulation of fruits during post - harvest management. In order to carry out this study search, multiple databases were used (Scielo, Redalyc, Elsevier, Scopus, Wiley Online Library, ScienceDirect, Springer). The importance of fruit maturation and its analysis at the molecular level has been of great interest in research, as it is a complex physiological and biochemical process leading to changes in appearance, texture, taste and aroma. Transcription factors have been shown to be of great importance, not only during early development, but also in the regulatory control of maturation and senescence; although there is progress in identifying these regulators, much remains to be investigated. In the near future, it will be possible to control the maturation of fruits and extend their shelf life by manipulating ethylene production using a transgenic approach.